2008
DOI: 10.1016/j.jep.2008.03.018
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulatory and anti-SARS activities of Houttuynia cordata

Abstract: The results of this study provided scientific data to support the efficient and safe use of HC to combat SARS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
240
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 285 publications
(250 citation statements)
references
References 26 publications
4
240
0
1
Order By: Relevance
“…(Saururaceae) is a perennial herb native to Southeast Asia with immense medicinal values. Traditionally, H. cordata is used for diuresis, detoxification, anti-viral, anti-bacterial, antileukemic, allergies, anaphylaxis and to tackle severe acute respiratory syndrome (Lai et al, 2010;Li et al, 2005;Lau et al, 2008;Lee et al, 2008). Recently, we reported that the ethanol fraction of H. cordata ethyl acetate (HC-EA) possess strong anti-oxidant and anti-neuroinflammatory properties (Park et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…(Saururaceae) is a perennial herb native to Southeast Asia with immense medicinal values. Traditionally, H. cordata is used for diuresis, detoxification, anti-viral, anti-bacterial, antileukemic, allergies, anaphylaxis and to tackle severe acute respiratory syndrome (Lai et al, 2010;Li et al, 2005;Lau et al, 2008;Lee et al, 2008). Recently, we reported that the ethanol fraction of H. cordata ethyl acetate (HC-EA) possess strong anti-oxidant and anti-neuroinflammatory properties (Park et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Quercetin 3-O-methyl ether and ophioglonin obtained from plants belonging to Ophioglossaceae genus have shown slight activity against HBV [50]. Since 1995 when antiviral activities against enveloped viruses were discovered in extracts of Houttuynia cordata [51], such as influenza, HIV, herpes, SARS and also in enteroviruses [51][52][53][54], 40 compounds have been isolated from the whole plant [55].…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that H. cordata has anti-microbial, immunostimulatory, diuretic, anticancer, sedative, anti-inflammatory, anti-allergic and antitussive effects (Park et al, 2005;Li et al, 2005;Lu et al, 2006;Kim et al, 2007). H. cordata has antiviral activities against herpes simplex virus type 1 (HSV-1), influenza virus and HIV as well as SARS-CoV (Hayashi et al, 1995;Chiang et al, 2003;Ono et al, 2006;Lau et al, 2008). Because H. cordata is very cheap and easily available in China and it may be one prospective natural products that can be used for treating PrV infection.…”
Section: Research Articlementioning
confidence: 99%